Identifying the genetic causes of phenotypically diagnosed Pakistani mucopolysaccharidoses patients by whole genome sequencing - Gul, Rutaba; Firasat, Sabika; Schubert, Mikkel; Ullah, Asmat; Peña, Elionora; Thuesen, Anne C. B.; Hussain, Mulazim; Staeger, Frederik F.; Gjesing, Anette P.; Albrechtsen, Anders; Hansen, Torben (Frontiers in Genetics, 2023)
Background Lysosomal storage disorders (LSDs) are a group of inherited metabolic diseases, which encompass more than 50 different subtypes of pathologies. These disorders are caused by defects in lysosomal enzymes, transporters, and other non-lysosomal proteins. Mucopolysaccharidosis (MPS) is the most common subgroup of LSDs in which the body is unable to properly breakdown mucopolysaccharides. The aim of the present study was to identify novel genes and pathogenic variants in families from diverse regions of Pakistan with clinically diagnosed MPS type I and MPS type II. Methods Clinical diagnosis identified 12 with MPS I and 2 with MPS II in 14 families and whole genome sequencing (WGS) was performed to identify the causative variations in 15 affected individuals. Twenty-two unaffected individuals including parents or normal siblings of patients were also sequenced. Putative causal variants were identified by co-segregation and functional annotation. Results Analysis of WGS data revealed ten novel and six previously reported variants in LSDs-associated genes (IDUA, GALNS, SGSH, GAA, IDS, ALDOB, TRAPPC4, MASP1, SMARCAL, KIAA1109, HERC1, RRAS2) and a novel candidate gene (ABCA5) for LSD-like phenotypes, which has previously been associated with symptoms strongly related with LSD in animal models. Conclusion Multigenic inheritance was found in several families highlighting the importance of searching for homozygous pathogenic variants in several genes also in families with a high degree of consanguinity.